Corporate Strategy on GMOs under Alternative Futures: The Case of a Large Food Retailer in Italy. (April 2016) - Passuello, Francesca; Boccaletti, Stefano
Summary: This article analyses the possible response strategies of a large Italian food retailer to alternative future scenarios for the segregation of GM and non‐GM products/ingredients in EU feed and food supply chains. Scenarios were developed by key EU feed‐food supply chain stakeholders during a 2‐day workshop held in Brussels in September 2014. Based on two major drivers, namely regulatory framework and perception of genetically modified organisms, stakeholders ended up with three scenarios: 1) Enabling regulatory framework, negative consumer's perception of GMOs; 2) Restrictive regulatory framework, positive consumer's perception of GMOs; 3) Restrictive regulatory framework, negative consumer's perception of GMOs. The retailer's strategy, which entails the certification of all the products sold under its private label as non‐GM, could be modified under different future scenarios. For example, with an increase in segregation costs due to a more restrictive regulatory framework and a positive perception of GMOs, the retailer may decide to differentiate private labels based on other safety/quality attributes or on the direct benefits for consumers of second generation quality‐enhanced GM products. If instead under a restrictive regulation the consumer's perception was still negative, the de facto ban of GMOs in the EU would probably cancel the retailer's exclusive reputational benefits from its voluntary non‐GM schemes, making this differentiation process unprofitable. Abstract : This article analyses the possible response strategies of a large Italian food retailer to alternative future scenarios for the segregation of GM and non‐GM products/ingredients in EU feed and food supply chains. Scenarios were developed by key EU feed‐food supply chain stakeholders during a 2‐day workshop held in Brussels in September 2014. Based on two major drivers, namely regulatory framework and perception of genetically modified organisms, stakeholders ended up with three scenarios: 1) Enabling regulatory framework, negative consumer's perception of GMOs; 2) Restrictive regulatory framework, positive consumer's perception of GMOs; 3) Restrictive regulatory framework, negative consumer's perception of GMOs.